Grounded theory and phenomenology - Mohd Arifin, Siti Roshaidai (2018)
This talk discussed on qualitative research designs and explained how to select a qualitative research method. It was delivered for postgraduate health-related students in International Islamic University Malaysia Kuantan Campus.